2011
DOI: 10.22495/cocv9i1c5art2
|View full text |Cite
|
Sign up to set email alerts
|

Does ownership structure affect firm performance? Evidence from Nigerian listed companies

Abstract: This paper examines the relationship between ownership structure and firm performance from the perspective of listed Nigerian companies. The sample comprises 73 companies listed on the Nigerian Stock Exchange for which relevant financial data is available for the period 2001 to 2007. The empirical results obtained through ordinary least squares (OLS) analysis provide evidence which suggests that dominant shareholding, ownership concentration, and foreign ownership structures have no significant effect on firm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The study indicated that managerial ownership had no discernible impact on firm value using OLS regression analysis. The research result is supported by many other researchers, namely, Switzer and Tangb (2009), Tsegba and Ezi-Herbert (2011), Liang et al (2012) etc. In addition, some other researchers, like Siala et al (2009) and Noor (2012), did not find any significant relation between these two variables.…”
Section: Corporate Governance and Firm Valuesupporting
confidence: 74%
“…The study indicated that managerial ownership had no discernible impact on firm value using OLS regression analysis. The research result is supported by many other researchers, namely, Switzer and Tangb (2009), Tsegba and Ezi-Herbert (2011), Liang et al (2012) etc. In addition, some other researchers, like Siala et al (2009) and Noor (2012), did not find any significant relation between these two variables.…”
Section: Corporate Governance and Firm Valuesupporting
confidence: 74%
“…These attributes provide the bureaucratic insularity needed to obviate (a) the manifestation of bureaucratic opportunism, and (b) the adverse consequences of the separation of ownership and control in the privatized firm. Put simply, core investors are those that have or must-have, the entrepreneurial bent, mechanisms, and incentives to own and manage the privatized enterprises (Tsegba and Herbert, 2011). and customers.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies also reveal that there is a significant relation between ownership concentration and performance (Shleifer and Vishny, 1997;Mang"unyi, 2011;Pivovarsky, 2003;Sanda, Mikailu and Garba, 2005;Joh, 2002;Xu and Wang, 1997). But some other previous studies disclose an absence of relation between ownership concentration and performance (Demsetz and Lehn, 1985;Shan and McIver, 2011;Sá nchez-Ballesta and Garcí a-Meca, 2007;Najjar, 2012;Tsegba and Ezi-Herbert, 2011). The relationship between ownership concentration and firm performance is still inconclusive.…”
Section: Statement Of the Problemmentioning
confidence: 95%